Assessing the influence of playing method on the outcome of basketball shooting ability - Zidan Dhia; Didi Suryadi; Y Touvan Juni Samodra; Mashud; Asriah Nurdini Mardiyyaningsih; Eko Saputra; Zsolt Németh; Asry Syam; Rezza Dewintha; Fazarudin (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. Shooting in a basketball game is the method of throwing the ball into the ring or basket to get points. As a result, extra treatment is required to improve kids' shooting abilities. The purpose of this study is to examine the effect of play method on basketball shooting ability results.